Ultra-high photo responsivity and self-powered photodetector in broad spectral range based on non-layered MnSe/WSe2 heterojunction - Zhao, Shuting; Ma, Xiurong; Cao, Xuanhao; Lei, Zehong; Yang, Yibin; Tao, Lili; Zheng, Zhaoqiang; Feng, Xing; Zhao, Yu (Frontiers in Materials, 2023)
Due to its good p-type semiconductor characteristics, MnSe has a great application prospect in high-performance electronic and optoelectronic devices. However, heterojunctions of MnSe still need to be deeply studied to improve its electrical and photoelectric properties. Here, it is reported that the two-dimensional (2D) MnSe/WSe2 heterojunction is structured by the non-layered MnSe nanosheets synthesized by chemical vapor deposition (CVD) method and the mechanically exfoliated layered WSe2. The heterojunction device exhibits a rectification effect and a current on/off ratio of 6557. Meanwhile, it has a broad spectral range response from ultraviolet (UV) to short-wave infrared radiation (SWIR) (300~2200 nm), and achieves an ultra-high responsivity of 156 A/W, along with an excellent detectivity of 2.21 × 1012 jones, and an outstanding external quantum efficiency (EQE) of 36400%. Moreover, the type II band alignment and the built-in potential in the MnSe/WSe2 heterojunction can facilitate the separation of the photoexcited electron-hole pairs, which enables the significant photovoltaic characteristics and self-powered photoswitching response. This work reveals the novel performance of the 2D MnSe/WSe2 heterojunction and a great potential in photoswitching, photodetector, and photovoltaic applications.